Effect of body mass index and rocuronium on serum tryptase concentration during volatile general anesthesia: an observational study (Clinics, 2020)
OBJECTIVE: Female sex, body mass index (BMI), and neuromuscular blocking agents are risk factors of perioperative hypersensitivity reactions. This study aimed to investigate the effect of rocuronium on serum tryptase concentrations during general anesthesia in overweight and obese women. METHODS: The study was conducted in two groups: Group I (n=66) underwent volatile anesthesia with rocuronium and group II (n=60) underwent volatile anesthesia without any muscle relaxant. Serum tryptase concentration (STC) measurements were performed at baseline (STC 0) and postoperatively (STC 1). ClinicalTrials. gov: NCT04035707 RESULTS: The highest median value of STC 0 was seen in obese patients (3.44 mg L-1) and it was significantly higher than in overweight (p=0.01) and underweight patients (p=0.03). The maximum STC 0 was observed in overweight patients (20.4 mg L-1). In group I, STC 0 in obese patients presented the highest median value (4.49 mg L-1), and was significantly higher than in overweight patients (p=0.03), and had significantly higher STC 1 than patients with normal BMI (p=0.04). STC 0 and STC 1 in overweight and obese female patients did not differ significantly between groups. STC 1 did not correlate with rocuronium doses. In group I, BMI positively correlated with the duration of rocuronium infusion (rho=0.37) and STC 1 positively correlated with BMI (rho=0.32). CONCLUSION: Excess weight and obesity predispose to higher preoperative serum tryptase values. Postoperative STC is not linked to rocuronium doses. BMI is the main determinant factor of STC during combined volatile general anesthesia.